Нікола Тесла – видатний винахідник - Школьник, В. А. (ХНУРЕ, 2020)
Nikola Tesla is a great inventor, whose life is shrouded in myths and legends, which we will consider in the study and find out what is a complete fiction. He has many achievements, inventions he invented himself, and others attributed to him after his death. His biggest mistake that ruined his career. Impossible goal due to an error. All these aspects created his current image and determined his fate.
Keywords: культурне розмаїття; українознавство; традиції; культура